Dopant‐Regulated Piezocatalysts Evoke Sonopiezoelectric and Enzymatic PANoptosis for Synergistic Cancer Therapy - Linhong Zhong; Xun Guo; Liming Deng; Xiaoting Wang; Hongye He; Nianhong Wu; Rui Tang; Liang Chen; Yu Chen; Pan Li (Advanced Science)
Abstract Piezocatalyst‐enabled sonopiezoelectric therapy offers noninvasive treatment with high spatiotemporal selectivity, yet existing piezocatalysts are limited by suboptimal efficacy, cancer cell resistance to oxidative stress, and biosafety concerns. Here, hafnia (HfO2), one of the only few FDA‐approved inorganic nanomaterials for clinical trials, is identified as a promising piezocatalyst with high translational potential for sonopiezoelectric and enzymatic PANoptosis‐boosted nanocatalytic therapy. Specifically, engineered transition metal‐substituted HfO2 nanocatalysts are synthesized to optimize piezoelectric and enzyme‐mimicking activities. Among these, Mn‐substituted HfO2 with a 20% Mn ratio (HMO) demonstrates superior performance in sono‐triggered reactive oxygen species generation, attributed to its reduced bandgap and increased oxygen vacancies. HMO also exhibits multiple enzyme‐mimicking activities, including peroxidase (POD), catalase (CAT), and glutathione peroxidase (GPx), amplifying oxidative stress through tumor‐specific catalytic reactions. These dual catalytic effects enable the activation of cancer cell PANoptosis to elicit a robust antitumor immune response. Biological evaluations show significant tumor suppression and antitumor immune responses by HMO‐mediated nanocatalytic therapy. Unlike utilizing the radiosensitization ability of HfO2 in the clinic, this work unveils the distinctive sonopiezoelectric effect and multienzymatic activities of HfO2‐based nanocatalysts for biomedical applications, holding the potential to overcome the challenges of radiation damage associated with radiotherapy.